Metadig: an application for self-regulated learning in distance education - Beatriz Ortega-Ruipérez (Edutec)
Metadig application has been designed and developed to facilitate self-regulated learning through metacognitive strategies in distance higher education teacher training. This study support application is based on the results gathered from a previous version of the application. On the one hand, based on how to pedagogically structure the support of metacognitive strategies, for which three basic functions are distinguished: goal selection and planning, monitoring, and self-assessment. On the other hand, improving the ease and suitability of use through validation by experts. In addition to incorporating all these proposals for improvement, this article provides a new study on the needs detected in the capacity for self-regulation in reading comprehension, study habits and the use of critical thinking in trainee teachers. In this way, the design process and the resulting development is based on both previous studies and how it can improve these three aspects (reading comprehension, study habits and critical thinking). It is concluded that a more suitable and user-friendly version has been obtained, and that it will improve the application of metacognitive strategies for self-regulated learning in terms of reading comprehension, study habits and critical thinking.